(untitled) (Research, Society and Development, 2025)
This writing results from a segment of a bibliographic research for the preparation of a Master’s dissertation in Education at the Federal University of Piauí (UFPI). It refers to the historical context of mathematics and mathematics education in Brazil, aiming to answer the following research question: what are the contributions of the historical context and mathematics education to the teacher’s work based on new curricular perspectives? The objectives are to deepen the knowledge about what mathematics and mathematics education are, as well as to reflect on this perspective in the teacher’s teaching practice and, consequently, in the child’s mathematical learning. The results clarify that it is essential for the teacher to know their pedagogical roots and that, through study and deepening, they can improve their practice, qualifying it according to the needs of the children, taking responsibility for the organization, execution, evaluation, and intervention in school processes. Being, in fact, a learning-teacher with creativity and critical thinking within the educational practice that should extend beyond the classroom walls.